Effectiveness of Specific Lumbar Stabilization Exercise for LBP among Postpartum Women: A Quasi-Experimental Study - Afrin Urme, Nadia; Alam, Fabiha; Jahan , Nusrat (Journal of Advanced Academic Research, 2021)
Background: Postpartum back pain is common, with up to 75% of women experiencing back pain immediately following birth due to ligament laxity and postural changes. Besides the lack of pelvic floor muscles strength, urine leakage problem during coughing and sneezing also arises in this condition. The purpose of this study was to explore the effect of stabilization exercise (SE) and Kegel exercise. Objective: To evaluate the pain intensity in rest and different functional activities before and after introducing spinal stabilization exercises in postpartum women with low back pain and also find out the effect of Kegel exercise. Study Design: A Quasi-Experimental (one group) pretest-posttest design was used. Methodology: 27 patients who were fulfill inclusion criteria within this study period with postpartum low back pain, attended at Gynecological and Women’s Health unit, CRP, Mirpur, Dhaka was purposively chosen to conduct the study. Spinal stabilization exercise was applied to the participants to find out the effectiveness of this exercise. Kegel exercise was also introduced who have urine leakage problem among 27 patients. Participants received the exercise for 45 minutes, 2 times a week & total 6 weeks. Besides this they performed the exercises at home 5 times a day also. A numeric pain rating scale was used to measure pain intensity in different functional activities such as swiping, squatting, chair sitting, heavy weight lifting, walking, and journey by bus or rickshaw, and stair climbing. Pain score was analyzed by calculating the "Wilcoxon Signed Ranked Test". Results: Results showed that relative improvement occurs in all participants in the experimental group. Pain scores on numeric pain rating Scale on different functional activities such as during toilet sitting, stair climbing, walking, during weight lifting, were relatively reduced which was also statistically significant (p≤ .05). Participants who have a urine leakage problem also recover from this problem. Conclusions: Lumbar stabilization exercises has effect on reducing pain and improving functional activities, and to solve the urine leakage problem Kegel exercise effective.